2020
DOI: 10.1097/aln.0000000000003437
|View full text |Cite
|
Sign up to set email alerts
|

Androgenic Modulation of the Chloride Transporter NKCC1 Contributes to Age-dependent Isoflurane Neurotoxicity in Male Rats

Abstract: Background Cognitive deficits after perinatal anesthetic exposure are well established outcomes in animal models. This vulnerability is sex-dependent and associated with expression levels of the chloride transporters NKCC1 and KCC2. The hypothesis was that androgen signaling, NKCC1 function, and the age of isoflurane exposure are critical for the manifestation of anesthetic neurotoxicity in male rats. Methods Flutamide, an an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 47 publications
3
43
1
Order By: Relevance
“…Both human 49 and animal 50 experiments suggest dose-dependent effects of testosterone on cognitive function. Although testosterone may have neuroprotective effects via inhibiting tau phosphorylation (present study), androgen receptor antagonism and gonadectomy may have neuroprotective effects via changes in chloride transporters 46 and being more developmentally similar to females, 47 respectively. Testosterone plus isoflurane could cause cognitive impairment in female neonatal rats via changes in chloride transporters.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Both human 49 and animal 50 experiments suggest dose-dependent effects of testosterone on cognitive function. Although testosterone may have neuroprotective effects via inhibiting tau phosphorylation (present study), androgen receptor antagonism and gonadectomy may have neuroprotective effects via changes in chloride transporters 46 and being more developmentally similar to females, 47 respectively. Testosterone plus isoflurane could cause cognitive impairment in female neonatal rats via changes in chloride transporters.…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies showed that an androgen receptor antagonist 46 or gonadectomy 47 attenuated isoflurane-induced behavioural deficiencies in neonatal male rats. Treatment with testosterone plus isoflurane caused cognitive impairment in neonatal female rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barnes maze testing is commonly used as an assessment of spatial memory and learning. 31 During the fourth week of recovery, rats were first subjected to a 4-day training period. For each training trial, the rat was placed in the center of the circular platform to freely explore for 240 sec.…”
Section: Methodsmentioning
confidence: 99%
“…The higher level of KCC2 and lower level of NKCC1 expression in the cerebral cortex of female rats compared with male rats are important evidence 76 . In another trial using androgen inhibitors, androgen regulation of KCC2 and NKCC1 expression levels was an important factor in the cognitive dysfunction caused by anaesthetic 77 …”
Section: The Role Of Neuroactive Steroids In Sex Differences In Devel...mentioning
confidence: 99%